Soundscapes by Nicolás Jaar. Between catastrophe and regeneration - Reyes Gil, Sebastián (Árboles y Rizomas, 2023)
This article addresses the productions of the Chilean-American musician Nicolás Jaar: his albums titled Cenizas y Telas (2020). Sound studies interrogate the hierarchical relationships between music, sound and noise. Using a multiplicity of records, Jaar generates a critique of our habitation in the world and the ways of connecting us with others. Through sounds, music, song lyrics, his recent work expresses tensions between, on one hand, solitude and isolation and, on the other hand, new possibilities of the collective.